2018
DOI: 10.1177/2041669518779098
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Color in Reading and Comprehension Tasks in Dyslexic Children and Adults

Abstract: We investigated the effect of chromatic variations on the reading process with normal and dyslexic readers. We demonstrate that color can induce wholeness, parts-whole organization and phenomenal fragmentation during reading and comprehension tasks within written texts made up of words and non-words in the following conditions: monochromatic (the whole text colored with only one color), word (each word colored in different color), half word (half word colored with a color different from the one of the second h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 64 publications
7
16
0
Order By: Relevance
“…This study gives further support to existing findings that colours may play an important role in the reading process [13,15,16,18,[32][33][34][35][36]. When normalization on the white background was performed (by subtracting white from each of the other background and overlay colours), systematic differences (on at least two colours) were found regarding HRV parameters (normalized SDNN, CVRR, and STD HR values), with second graders scoring higher on these parameters, Table Conflicts of Interest: "The authors declare no conflict of interest."…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study gives further support to existing findings that colours may play an important role in the reading process [13,15,16,18,[32][33][34][35][36]. When normalization on the white background was performed (by subtracting white from each of the other background and overlay colours), systematic differences (on at least two colours) were found regarding HRV parameters (normalized SDNN, CVRR, and STD HR values), with second graders scoring higher on these parameters, Table Conflicts of Interest: "The authors declare no conflict of interest."…”
Section: Discussionsupporting
confidence: 89%
“…Jansky [14] reported the case of a student with a reading deficit who was able to recognize words printed on yellow paper, but unable to recognize words printed on white paper. Previous studies considered the influence of background-, text-or overlay-colour on the actual reading process in children [13,15,16]. While more recent studies have shown that colours do not influence the reading process and that this could be a placebo [17], others have found that colours may be particularly effective for early readers in schoolage children [18].…”
Section: Introductionmentioning
confidence: 99%
“…This study gives further support to existing findings that colours may play an important role in the reading process [13,15,16,18,[32][33][34][35][36]. When normalization on the white background was performed (by subtracting white from each of the other background and overlay colours), systematic differences (on at least two colours) were found regarding HRV parameters (normalized SDNN, CVRR, and STD HR values), with second graders scoring higher on these parameters, Table 3.…”
Section: Figure 2 Sdnn Cvrr and Std Hr By Grade And Colour (Normalisupporting
confidence: 89%
“…Jansky [14] reported the case of a student with a reading deficit who was able to recognize words printed on yellow paper, but unable to recognize words printed on white paper. Previous studies considered the influence of background-, text-or overlay-colour on the actual reading process in children [13,15,16]. While more recent studies have shown that colours do not influence the reading process and that this could be a placebo [17], others have found that colours may be particularly effective for early readers in school-age children [18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our results showing enhancement of reading performance when color (i.e., timbre) was added to audemes are in contrast to some of the results obtained when adding color to visually presented letters. A recent study [68] explored the effect of reading with the addition of color in dyslexics as well as normal readers, both adults and children. When each whole-word was colored in a different color, reading was enhanced in all groups compared to a monochromatic condition, possibly due to the fact that color strengthened the perceptual grouping of words.…”
Section: Plos Onementioning
confidence: 99%